Phases of International Dispute Settlement and the Need for Adaptive Approach - Akeem Saliu; Adeola Adebisi (Britain International for Academic Research (BIAR-Publisher), 2022)
The paper revisits different perspectives on how international disputes are resolved without escalating into war. For example, there are articles on how these conflicts develop and what peace looks like, as well as the media's role in encouraging or discouraging violent conflict. By evaluating the involvements of state actors and non-state actors in conflict resolution, the study submits that efforts to make an effective peacekeeping doctrine by the United Nations (UN) have been faced with challenges by powerful states which hold the highest stakes in global politics. The world has a crucial stake in resolving conflicts among states without resorting to war because of the many deaths, economic loss, humanitarian crises, and other consequences of war across the globe. The UN has established a global agenda to help states that are or could be involved in violent conflicts. Drawing from the findings, the paper concludes that the usage of force during the process of peace and as a panacea to dispute resolution should be re-examined in view of the irrelevance of force in the current international order. Apart from making international institutions functional, disputants should be made prominent throughout the peace process and be adaptive to the consequences of the dispute and its effects on the community and the belligerents themselves.